Arranged-demand irrigation scheduling with nonidentical discharges - Anwar, Arif A.; Haq, Z.U. (American Society of Civil Engineers, 2016)
Several irrigation water delivery methods are in practice in irrigated agriculture throughout the world, and a variety of classifications have been suggested by different researchers. Demand, arranged-demand, and rotation are the three main types of irrigation schedules/delivery methods. Irrigation systems may also be classified as either sequential or simultaneous. Supplying water sequentially to farmers according to their requested times constitutes an irrigation scheduling problem analogous to the classical earliness/tardiness single machine scheduling problems in Operational Research (OR). In this paper, the authors describe an irrigation scheduling problem analogous to the complex multimachine scheduling problem. The authors develop a genetic algorithm (GA) and test this algorithm against solutions obtained from an integer program to draw conclusions about the solution quality of the GA. The researchers demonstrate the potential of this GA through an engineering application of the Maira Branch Canal. The authors show that if this canal is operated at a constant discharge, the arranged-demand schedule requires the canal to be operated at 75% of the discharge required if this canal were operated on an on-demand schedule.